2018
DOI: 10.1038/s41598-018-29434-2
|View full text |Cite
|
Sign up to set email alerts
|

Streptozotocin-induced β-cell damage, high fat diet, and metformin administration regulate Hes3 expression in the adult mouse brain

Abstract: Diabetes mellitus is a group of disorders characterized by prolonged high levels of circulating blood glucose. Type 1 diabetes is caused by decreased insulin production in the pancreas whereas type 2 diabetes may develop due to obesity and lack of exercise; it begins with insulin resistance whereby cells fail to respond properly to insulin and it may also progress to decreased insulin levels. The brain is an important target for insulin, and there is great interest in understanding how diabetes affects the bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Immunofluorescence Analysis of Insulin in the Pancreatic β-Cell of T2DM Mice. Since the previous study reported that insulin is secreted by β-cells in the pancreas, which is one of the most important metabolic hormones to control blood glucose, 38,39 we investigated the ability of insulin secretion and the potential effects of MTNP on pancreatic βcell injury in diabetic mice. Immunofluorescence (IF) analysis was utilized to measure the expression of insulin in the pancreas, in which the anti-insulin antibody was used to determine the insulin expression.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Immunofluorescence Analysis of Insulin in the Pancreatic β-Cell of T2DM Mice. Since the previous study reported that insulin is secreted by β-cells in the pancreas, which is one of the most important metabolic hormones to control blood glucose, 38,39 we investigated the ability of insulin secretion and the potential effects of MTNP on pancreatic βcell injury in diabetic mice. Immunofluorescence (IF) analysis was utilized to measure the expression of insulin in the pancreas, in which the anti-insulin antibody was used to determine the insulin expression.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Streptozotocin and alloxan administration can induce hyperglycemia by increasing β-cell death in non-obese rats. However, their administration increases β-cell death through elevated reactive oxygen species, removal of which can reduce diabetic severity during treatment [ 36 , 37 ]. They also induce neuronal cell death [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…affects hepcidin level that depends on peripheral insulin resistance rather than decrease in insulin secretion. [24][25][26] Hepcidin, a hormone that inhibits the absorption of iron from the intestine, may show increased levels in T2DM patients due to the increase of insulin secretion stimulated by the high level of blood glucose. 27 In addition, high hepcidin level may have resulted from the stimulation of the extrahepatic pathway, specifically from macrophages, as a result of inflammatory process induction.…”
Section: Conflict Of Interestmentioning
confidence: 99%